Girls. The complete second season [videorecording (DVD)] - Dunham, Lena, 1986-; Williams, Allison, 1988-; Driver, Adam; Kirke, Jemima; Mamet, Zosia, 1988- (HBO Home Entertainment, 2013)
A scripted half-hour series focuses on a group of 20-something's in NYC. Season Two episodes, Hannah forges ahead in her writing pursuits, but her enthusiasm is tempered by the responsibility for Adam; Marnie needs her best friend and former roommate; Jessa returns from her honeymoon in Mexico; Shoshanna takes charge of her new identity; and Ray has an out-of-sight, out-of-mind attitude.